Ischemic Preconditioning Does Not Alter Performance in Multidirectional High-Intensity Intermittent Exercise - Zinner, Christoph; Born, Dennis-Peter; Sperlich, Billy (Frontiers in Physiology, 2017)
Purpose: Research dealing with ischemic preconditioning (IPC) has primarily focused on variables associated to endurance performance with little research about the acute responses of IPC on repeated multidirectional running sprint performance. Here we aimed to investigate the effects of IPC of the arms and the legs on repeated running sprint performance with changes-of-direction (COD) movements. Methods: Thirteen moderately-to-well-trained team-sport athletes (7 males; 6 females; age: 24 ± 2 years, size: 175 ± 8 cm, body mass: 67.9 ± 8.1 kg) performed 16 × 30 m all-out sprints (15 s rest) with multidirectional COD movements on a Speedcourt with IPC (3 × 5 min) of the legs (IPCleg; 240 mm Hg) or of the arms (remote IPC: IPCremote; 180–190 mm Hg) 45 min before the sprints and a control trial (CON; 20 mm Hg). Results: The mean (±SD) time for the 16 × 30 m multidirectional COD sprints was similar between IPCleg (Mean t: 16.0 ± 1.8 s), IPCremote (16.2 ± 1.7 s), and CON (16.0 ± 1.6 s; p = 0.50). No statistical differences in oxygen uptake (mean difference: 0%), heart rate (1.1%) nor muscle oxygen saturation of the vastus lateralis (4.7%) and biceps brachii (7.8%) between the three conditions were evident (all p > 0.05). Conclusions: IPC (3 × 5 min) of the legs (220 mm Hg) or arms (180–190 mm Hg; remote IPC) applied 45 min before 16 × 30 m repeated multidirectional running sprint exercise does not improve sprint performance, oxygen uptake, heart rate nor muscle oxygen saturation of the vastus lateralis muscle when compared to a control trial.